Afghanistan - State Building, Sustaining Growth, and Reducing Poverty : A Country Economic Report - World Bank (Washington, DC, 2013)
This is the first Economic Report on Afghanistan by the World Bank in a quarter-century. It is intended to contribute to a better understanding of the core challenges that lie ahead for the country and key strategic priorities for national reconstruction. It focuses on the conceptual frameworks, policies, and institutions that will be needed to achieve core national objectives of state-building; sustained rapid, broad-based economic growth; and poverty reduction. Analysis of the Afghan economy is hindered by severe data limitations (discussed in the Statistical Appendix) and is challenged by the conflict-related economic structure and dynamics that have emerged during the past two decades. Nevertheless much has been learned about how the Afghan economy functions, at least in qualitative and institutional terms. The report also draws on the great volume of work done on individual sectors and topics by the Government and partners. This report starts with a description and analysis of the Afghan economy and it s recent performance (Chapter l), and the poverty situation (Chapter 2). Chapter 3 outlines a strategy for growth and poverty reduction, based on the NDF/SAF, and puts forward key strategic priorities and directions for implementation. State-building, discussed in Chapter 4, lies at the core of Afghanistan's reconstruction as well as progress on political, security, and other fronts. Chapter 5 addresses the development of the private sector, which will have to be the engine of growth and poverty reduction in Afghanistan. Agriculture, covered in Chapter 6, comprises half of the economy and will play a crucial role. Chapter 7 examines Afghanistan's opium economy, which has some short-term economic benefits but very serious adverse effects on state-building and security. Chapter 8 looks at delivery of social services, a key component of the poverty reduction strategy, including the gender dimension. Social protection--strategies and programs to assist the poorest and most vulnerable members of Afghan society--is discussed in Chapter 9. Chapter 10 concludes with a summary of priorities for action, implementation constraints, prospects, and risks.